Desenvolvimento de um Sistema em Fuxos Automatizado para Determinação de Metais-traço em Matrizes Aquosas - Cádmio como metal teste - Soares, Tiago Furlanetto (2011)
This work presents a automatic flow system for enrichment of aqueous samples based in solid-liquid extraction. Two syringe pumps, driven solutions of samples, complexation agent (bromocresol green 0.01%), eluent (ethanol), through a flow system, basicaly formed by six three way solenoid valves (Cole-Parmer-USA), one mini-column loaded with Amberlite XAD16 and a sampler mini-funeel. The syringes and valves were controled from a PC - AT386 with a paralel interface (ACL 8111-Adlink) and a serial (RS232C) interface. Also was emploied a interface based in ICULN2803A (SGS-Thomson Microelectronics). The system was optimized for Cd ²+ like test metal, however the proposed system may to be used for any metalic ion after definition of chemical parameter, as like: kind of metal, complexation agent, solid suport and eluent. The detection was performed off-line by flame atomic absorptiom spectrometry. For 10 mL of Cd²+ standards in 50 to 500 μg Lˉ¹ range and 200 μL of eluate was obtained a enrichment factor of 10.6 with a detection limit of 15 μgLˉ¹ and analytical frequency of five determinations/hour.